Pendampingan Pembelajaran Literasi, Numerasi, dan Adaptasi Teknologi pada Masa Pandemi Covid-19 di SDN 2 Kutorembet - Pristi Sukmasetya; Prihatin Dwihantoro; Ardhin Primadewi; Maimunah; Resa Arif Yudiyanto; Rofi Abul Hasani; Ika Arthalia; Safira Ayu Muthi'ah (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2022)
Learning Literacy, Numeration, and Technology Adaptation is now very important for students, especially in elementary school, to strengthen the concept of logical thinking. Literacy is critical because it relates to the child's ability to listen, review, speak to observe so that they can communicate well without being affected by the subject of the audience. At the same time, numeracy skills are defined as the ability to interpret, access, use and link the concepts in mathematics in their application. However, in fact for implementing literacy and numeracy learning in schools is still considered a challenge in itself, colliding with limited access and materials, especially in this Covid-19 pandemic condition. So, this service activity was carried out by maximizing the literacy and numeracy learning mentoring process at the Kutorembet SDN placement location, which took place from August 2, 2021 to December 17, 2021. Activities carried out include teaching and learning activities to provide academic assistance. The key teaching and learning activities focus on literacy and numeracy education activities. Activities to help adapt technology are realized by showing educational videos to students and assistance in ANBK activities, as well as school administrative assistance activities which are realized by maximizing the function of the school library. This activity is carried out online and offline, considering the conditions of the COVID-19 pandemic, which require actions to occur in a hybrid manner. From this activity, it was found that the results of improving literacy and numeracy for elementary school students at SDN 2 Kutorembet and also additional literacy for classroom teachers in preparing existing learning media.